On legal subterfuge and the so-called "lawfare" debate - Sadat, Leila Nadya; Geng, Jing (Case Western Reserve journal of international law, 2010)
The term "lawfare" is a contentious and ideologically charged concept as evidenced in its contemporary, popular usage. There are many nuances to the term, though lawfare is generally defined as a tactic of war where the use of law replaces the use of weapons in the pursuit of a military objective. Lawfare proponents increasingly claim that adversaries of the United States are manipulating the rule of law to undermine democracy and national security. The term "lawfare" is applied to contexts as varying as habeas corpus petitions of Guantanamo detainees, lawsuits by individuals subjected to torture or extraordinary rendition, universal jurisdiction, hate speech litigation, and the Goldstone Report. This essay explores some preliminary etymological background on the term to explain its current use and misuse. It argues that lawfare is an unhelpful term that has no real fixed meaning. Lawfare is a concept that may be catchy in media communications, but its distorted usage has substituted careful analysis and discourse with a fruitless -- and even dangerous -- rhetorical debate. The notion that terrorists are using the rules of humanitarian law, domestic law and human rights law to gain improper advantages over the United States undermines general respect for the rule of law. Alternatively, equal application of domestic and international legal rules and legal processes to both rich and poor, powerful and weak, creates a better ordered community rooted in peace and stability. Ultimately, this essay concludes with some concrete suggestions on how to move forward from the usage of this singularly unhelpful term. [PUBLICATION ABSTRACT]